An extremely rare case of malignant jejunal mesenteric inflammatory myofibroblastic tumor in a 61-year-old male patient: A case report and literature review - Al Shenawi, Hamdi; Al-Shaibani, Salamah A.; Al Saad, Suhair K.; Al-Sindi, Fedaa; Al-Sindi, Khalid; Al Shenawi, Noor; Naguib, Yahya; Yaghan, Rami (Frontiers in Medicine, 2022)
Introduction Mesenteric inflammatory myofibroblastic tumor (IMT) is a rare, mostly benign tumor that affects children, adolescents, and young adults predominantly. IMT is mostly encountered in the lung. We report a case of malignant jejunal mesenteric IMT in a 61-year-old male patient. The patient presented with vague abdominal pain and generalized weakness. MRI revealed a mesenteric mass displacing the attached jejunum. Surgical resection was curative. Discussion An extensive literature review was performed to update and further analyze the already available data. 35 cases with mesenteric IMT were reported previously. Only 5 cases of jejunal mesenteric IMT were reported. Mesenteric IMT demands vast effort to reveal the diagnosis due to its vagueness in the clinical presentation. Mesenteric IMT resembles each other in plenty of pathological and immunohistochemical characteristics. Conclusion To the best of our knowledge, this is the first case of malignant jejunal mesenteric IMT in the elderly. Surgical resection was curative.